La revolución también es una calle. De frentes, fronteras y cruces culturales - Ricardo Morales Lira; Alfonso García Cortéz (Estudios sobre las Culturas Contemporáneas)
Like some fields, public agents and cultural offerings have developed at the Tijuana border. In what form have social spaces of specialization in uiban cultural practices been created? How do collective identities arise, change, become transformed and conserved through the constant crossing of ctiltural fronts and borders in social spaces like the street? These are some of the questions that serve as the point of departure for this woik which attempts to relate, historically and reflexively, from one of the key spaces of Tijuana where the most diverse cultural practices are taking place: Revolution Avenue.